Spatial analysis on local food truck in KL - Ramdan, Nuur Hafizah; Abdul Rahman, Julaila; Zakariya, Khalilah (Kulliyah of Architecture and Enviromental Design, International Islamic University Malaysia, 2019)
In their continuing search for competitive differentiation, the Food and Beverages (F&B entrepreneurs) are now turning mobile vendor including food truck as new and promising business proposition. While the growth of food truck in the current trend, the vendor's creativity and consumer’s demands influencing the evolving of food truck business in Malaysia. 3 kinds of food truck categories have been observed; Local food, western food and beverages. Space allocation is one of the most important and crucial part to create the spacious food truck interior for convenience of food truck vendor to operate their business. The mobile vendor chronology from the year 70s until 20s shows that there several movement designs in term of food truck space allocation and user circulation. This study aims to analytical study on the movement advancement of food truck chronology from international and local food truck and to find out the factor affected the circulation and interior design of the food truck. By using the pilot study and observation of line up study methods the result shows that type of food truck and type of food servings influenced the interior circulation and safety issue of the food truck operation. The findings show that there are few factors that affected the changing of the food truck interior circulation, and the study should be carry further deeply into universal design study that will include all type of users and possibly vendors with disabilities.